Kepemimpinan Kepala Madrasah (Studi Kasus Kepemimpinan Kepala Madrasah di Kabupaten Muaro Jambi Provinsi Jambi) - Jailani, M. Syahran; Nasution, Rahmad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This study aims to investigate the approach of principals managerial leadership in elementary Islamic school level at Muaro Jambi district, Jambi province. The leadership model where sets the headmaster as a manager who adopted modern management theories. In practical not all the modern management theories can apply in the leadership of headmaster. In this research, the data collection techniques by using observation, interviews, documentation. The analyzing data by using Miles and Huberman (1994: 16-18): data reduction, data display, and verification or conclusion. The findings of the research revealed managerial leadership at the school in the District Muaro not been implemented as expected and has not been effective. The findings also revealed that leadership success is very determined as follows: (1) honesty, (2) openness, (3) exemplary, (4) wisdom, (5) mindset, and (6) the effect of the leader himself.